PENGEMBANGAN MATERI AJAR MENULIS TEKS PIDATO BERBANTUAN GOOGLE CLASSROOM PADA SISWA KELAS VIII SMP - Br Surbakti, Nabila; Prihasti Wuriyani, Elly (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop teaching materials for writing speech texts using Google Classroom for eighth-grade students at SMP Negeri 1 Labuhan Deli and determine their feasibility and practicality. The research used a research and development (R&D) model with a 4D model, including the define, design, and develop stages. This study did not reach the dissemination stage. The subjects consisted of material experts, media experts, teachers, and 10 eighth-grade students at SMP Negeri 1 Labuhan Deli. The data collection instruments used were validation questionnaires from material experts and media experts to measure product feasibility, and teacher and student response questionnaires to measure product practicality. The data obtained were analyzed descriptively using quantitative and qualitative methods. The results of the study showed that the developed teaching materials met the feasibility criteria, with a validation percentage of 90.38% from material experts and 91.66% from media experts, both of which fell into the "very feasible" category. Furthermore, the results of the practicality test showed that teacher responses were 94.4%, categorized as "very practical," while student responses were 88.95%, categorized as "practical." The resulting product was teaching materials for writing speeches using Google Classroom, presented through a material menu, complete with learning objectives, material descriptions, examples of speeches, writing assignments, and reflections. Therefore, the developed teaching materials were deemed feasible and practical for use in teaching speech writing in eighth-grade students at SMP Negeri 1 Labuhan Deli.